Identifikasi Dan Pemetaan Tanaman Aren (Arenga Pinnata) Plus Di Hutan Pendidikan Konservasi Terpadu Tahura Wan Abdul RachmanIdentifikasi Dan Pemetaan Tanaman Aren (Arenga Pinnata) Plus Di Hutan Pendidikan Konservasi Terpadu Tahura Wan Abdul Rachman - Elya Artika; Duryat Duryat; Susni Herwanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Great Forest Park of Wan Abdul Rachman has a suitable conditions for plus palm sugar (Arenga pinnata) plant, so that its plant has a great potential to be developed in the region. Related to its cultivation and development, the identification of plus palm sugar plant is needed in order to fulfill demand the planting material. The purpose of this research are to identify, to figure out the deployment location, and to create a spreading map of plus palm sugar plant. This research was conducted in the Integrated Conservation Education Forest At Great Forest Wan Abdul Rachman, collection of data was conducted by interview to all of the plus palm sugar plant tappers in the region, in order to collect the information about all the plus palm sugar plant that has productivity more than 15 liters/tree/day. The obtained result from the interview then it was verificated and categorized based on plus palm sugar plant criteria. Data of plus palm sugar plant, then recorded and overlayed in the map of base area At Great Forest Wan Abdul Rachman, to create a spreading map of plus palm sugar plant. This research showed that there were 16 plus palm sugar plant identified. Most of the plus palm sugar (93.75 %) growth on altitude of 400 - 525 upper sea level.Palm plus that have high productivity its those that growth with less of competition and managed in a good way. Keywords:Tahura Wan Abdul Rachman, distribution map, identification, plus palm sugar plant